Marble Decoration of the Interior of the Catholiсon Hosios Loukas in Phocis - Shcherbakova, Aleksandra V. (Actual Problems of Theory and History of Art, 2013)
In this article we are discussing specifics of the marble revetment of the interior of the Hosios Loukas Catholicon, highlighting its role in the architectural image of the temple.
Keywords: Byzantine architecture; Hosios Loukas; marble decoration; history of architecture